Waterbird synchrony across Australia's highly variable dryland rivers – Risks and opportunities for conservation. (March 2020) - Bino, Gilad; Brandis, Kate; Kingsford, Richard T.; Porter, John
Abstract: Understanding the mechanisms which drive large scale population dynamics of highly mobile organisms, such as birds, is as challenging as it is important. For waterbirds depending on Australia's dryland rivers, little is known about the spatiotemporal dynamics and degree of population synchrony, despite its importance for conservation theory and practice. We examined spatial synchrony in 50 waterbird species using aerial survey data over the past three decades (1983–2016), across two of Australia's largest river basins, representing almost a third of the continent using state-space models. There was broad synchrony in the responses of Australian waterbird numbers in wetlands, varying among functional response groups, reflecting the spatiotemporal mosaic of flooded wetlands across multiple scales. Ducks, the most abundant functional response group, and herbivorous waterbirds displayed strong spatiotemporal synchrony within and between the Lake Eyre Basin and Murray-Darling Basin, while synchrony of piscivores was patchier. In contrast, large waders and particularly shorebirds had poor synchronicity. While rainfall among catchments within river basins was highly correlated, streamflow was correspondingly weakly correlated in the Murray-Darling Basin primarily because river regulation had separated rainfall from flow and inundation, potentially compromising waterbird response triggers. There are clear conservation implications for wetlands and their waterbird populations, principally the protection of natural flow regimes in the Lake Eyre Basin and where needed, restoration of environmental flows in the Murray-Darling Basin. Also, management of waterbirds needs to often extend beyond the boundaries of basins.